Las estrategias metodológicas para lograr un buen rendimiento académico en el colegio “Pio Jaramillo Alvarado” de la ciudad de Loja, modalidad a distancia en el año lectivo 2013 – 2014. Lineamientos alternativos - Moncayo Ortiz, Gioconda Soraya (2015)
This research called “LAS ESTRATEGIAS METODOLÓGICAS PARA LOGRAR UN BUEN RENDIMIENTO ACADÉMICO EN EL COLEGIO “PIO JARAMILLO ALVARADO” DE LA CIUDAD DE LOJA, MODALIDAD A DISTANCIA, EN EL AÑO LECTIVO 2013 – 2014. LINEAMIENTOS ALTERNATIVOS” general objective: Determine the use of methodological strategies for successful academic performance in distance learning in young College "Pio Jaramillo Alvarado" Distance Learning of the City of Loja. It is descriptive and explanatory. The methods used were scientific, descriptive, analytical, synthetic. As the survey technique was used, and the instrument of the questionnaire was applied to 23 teachers; and 96 students of first, second and third year of high school. Report cards (book), the results were 84% of teachers use traditional methods of study, distributed also observed: language strategies, reading, analysis, summary, synthesis scheme, all framed drawing dictation, move stuff, duties, thus demonstrating poor performance in students. In the informants it was determined that 84% of teachers do not use teaching strategies according to the mode of study. The results of observation the teacher to handle book teachers, 65% of freshmen high school, 58% the second high school and 66% have problems third high school in academic performance